Conduction disorders in the setting of transcatheter aortic valve implantation: a clinical perspective. Issue 7 (8th March 2013) - Fraccaro, Chiara; Napodano, Massimo; Tarantini, Giuseppe
<x xml:space="preserve">Abstract</x> The presence of periprocedural conduction disorders (CDs) and the need for permanent pacemaker (PPM) after transcatheter aortic valve implantation (TAVI) are frequent findings in clinical practice. Notwithstanding, robust information on the prognostic and therapeutic implications of these complications are lacking. The newly occurrence of CD after TAVI seems related to the trauma of the conduction system during procedure. On the contrary, major predictors for PPM implantation after TAVI seem to be the use of CoreValve prosthesis (Medtronic, Minneapolis, MN) and the presence of CD before TAVI. An accurate pre‐TAVI screening, careful valve implantation, as well as post‐TAVI monitoring must be pursued to prevent avoidable PPM implantation. The aim of this report is to analyze the available data on this field and to propose some practical clinical tips to prevent or to manage these complications. © 2013 Wiley Periodicals, Inc.